Relative Analysis of Price Discovery Tools Operative in Indian Capital Market - Aggarwal, Monika (Indian Journal of Finance, 2008)
Present Indian Capital Market is known as strong&vibrant component of Indian financial system. Many governmental and non-governmental efforts are being put to bring it at par with International Financial Market. Establishment of SEBI as an apex regulatory body has proved to be a revolutionary step towards bringing the structural changes in order to regain the confidence of Indian investors&to attract the foreign investment. In this direction, the primary market has witnessed a number of reforms over the time. Major changes involved abolition of control over pricing, designing and tenure of instruments etc. SEBI has introduced various stringent disclosure norms. One important reform, which needs consideration, is "Pricing of Issue." It is the most critical element of any public issue. Under CCI regime, all companies coming with a public issue had to price their issue based on CCI formula. It was felt to be an anti-market practice because all companies whether fundamentally sound or not had to price their issue very conservatively. As a result, all the issues coming into market were easily oversubscribed leaving few scopes for further rise in price on its listing. In 1992, CCI was abolished and companies were allowed to price their issue freely subject to some disclosure requirements. Following this, the guidelines have been provided that allow the issuer to decide the price in consultation with merchant banker. There is no price formula stipulated by SEBI. However, company and merchant banker are required to give full disclosures of the parameters which they had considered while deciding the issue price. Basically there are two modes of pricing the offer: (a) Fixed Price Method (b) Book Building Method. In case of Fixed Price offer, an issuer company is allowed to freely price the issue. The basic of issue price is disclosed in offer document. The company can mention a price band of 20% (the cap in price band should not be more than 20% of floor price) in draft offer document filed with SEBI and actual price can be determined at a later date before filing of final offer document with SEBI/ ROC. Whereas Book Building is a process by which a demand for securities proposed to be issued by a body corporate is elicited&built up and price for securities is assessed on the basis of bids obtained for quantum of securities offered. So, under Free Pricing Era, companies can freely price their issues either through Fixed Price or Book-Building. Book Building is assumed to be optimum price discovery Mechanism over last four five years. In this context, this paper is an attempt to analyse the preference of Book Building process&Fixed Price Method for pricing the issue&also an attempt has been made to study the impact of price method on the performance of the issue.